De quelques aspects des dimensions politiques et économiques des circulations migratoires au Sahara central - Julien Brachet (L’Année du Maghreb)
This article offers a local perspective on the nature and recent transformations of the Saharan migration system, showing how such policies affect those who live or travel through these areas. An illustration of the historical significance of intra-African migration systems for the economic development of North-West Africa is followed by an analysis of new patterns of migrations that have emerged since the 1990s throughout central Sahara. A brief outline of the externally driven legal and institutional frameworks that govern the movements of people in this area is provided, highlighting how states deal with local migration systems, and what are their possible local impacts in central Sahara.